PENGHINAAN TERHADAP PENGADILAN VERSUS KEBEBASAN PERS - Manan, Bagir (Jurnal Hukum dan Peradilan, 2015)
Press is manifestation of public soverignty to the power. Press control function covers critic, analytic, and information to the public, so all the activities which are from branches of power based on the public wish and hope. Freedom of press is limited by the press law and code of conduct. The freedom of press can not be used for humaliation, harassment, or interference of judicature process. Press must respect the institution and independency of judiciary.Keywords : Contempt of Court, Freedom and Press